2013
DOI: 10.1111/pde.12190
|View full text |Cite
|
Sign up to set email alerts
|

Late Rebound of Infantile Hemangioma after Cessation of Oral Propranolol

Abstract: Propranolol has become the first line of treatment for infantile hemangiomas (IHs), with a high response rate, but rebound growth after cessation of propranolol has been reported, primarily in the first year of life. We sought to determine the frequency and associated factors leading to late regrowth after successful treatment at an age when the proliferative phase has usually ceased. We retrospectively reviewed the clinical charts, serial photographs, and radiologic images of children with rebound IH occurrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 12 publications
3
47
1
Order By: Relevance
“…Their finding of increased rebound in deep or mixed IH and segmental IH is consistent with other reports, [6][7][8] as is the increased risk of rebound observed in girls 2,[6][7][8] The aforementioned hemangioma subtypes may represent a unique subpopulation of IH programmed to proliferate longer. 11,12 In a series of IH with prolonged growth by Brandling-Bennett et al, 11 all 23 lesions were on the head and neck, another feature found in the current study; in that series, nearly 40% of IH involved the parotid gland, a detail not included in the current report.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Their finding of increased rebound in deep or mixed IH and segmental IH is consistent with other reports, [6][7][8] as is the increased risk of rebound observed in girls 2,[6][7][8] The aforementioned hemangioma subtypes may represent a unique subpopulation of IH programmed to proliferate longer. 11,12 In a series of IH with prolonged growth by Brandling-Bennett et al, 11 all 23 lesions were on the head and neck, another feature found in the current study; in that series, nearly 40% of IH involved the parotid gland, a detail not included in the current report.…”
supporting
confidence: 80%
“…Several previous studies report a higher rebound rate with shorter durations of OP therapy, 2, 6, 13 although in others this association is less clear. 7 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rebound growth of IH has been observed in 6% to 25% of children, often well after their first birthday, leading some clinicians to wean propranolol over weeks to months. [185][186][187][188][189] Rebound growth may be more likely in patients whose IH exhibited a long proliferative stage and a large subcutaneous component. 185 In such cases, reinitiation of therapy for variable periods of time may be necessary.…”
Section: Duration Of Therapymentioning
confidence: 99%
“…β-blockers have recently been introduced as a safe and effective treatment for IH [8][9][10][11]. However, their use is not without risk, and not all tumors respond to these drugs [12,13]. These issues have spurred extensive research to clarify the signaling pathways implicated in hemangioma neovascularization in the hope that a greater understanding of its molecular pathogenesis will reveal new strategies to tackle IH.…”
Section: Introductionmentioning
confidence: 99%